Learner’s Perceptions on Vocabulary Learning Strategies: A Qualitative Single-Case Study - Amalia, Faridanisa Zulfa; Sulistyani, Ummi Nur Laila (Universitas Negeri Semarang, 2025)
This qualitative single-case study investigates an Indonesian EFL learner’s perceptions of vocabulary learning strategies, an important but often overlooked aspect of language learning. Despite vocabulary being the core of mastering a foreign language, learners' perceptions remain underexplored, particularly in qualitative research. This study aims to address that gap by examining a single participant’s use of and perceptions of vocabulary learning strategies. Data were collected through a 32-item Likert-scale questionnaire based on Schmitt’s (1997) taxonomy and semi-structured interviews guided by the Cognitive-Affective-Conative (CAC) perception model by Schiffman & Kanuk (2004). The findings revealed a contradictory perception: although the participant acknowledged the effectiveness and practicality of vocabulary learning strategies, she also expressed a belief that exposure to language is more critical than strategic vocabulary learning. The participant showed a clear preference for social strategies and incidental learning, which she found more enjoyable and versatile than memory strategies. Her cognitive, affective, and conative responses suggest that motivation in vocabulary learning are deeply influenced by strategy flexibility and learner autonomy. The study concludes that EFL learners should be introduced to various vocabulary learning strategies early in their education, and educators should design instruction that respects learners’ preferences. This research highlights the importance of the learner’s perspective as an input to the growing literature in the EFL learning context and recommends broader, multi-participant qualitative studies in the future.